Dual-band skin-adhesive repeater antenna for continuous body signals monitoring - João M. Felício; Costa, J. R.; C. A. Fernandes (IEEE Journal of Electromagnetics, RF and Microwaves in Medicine and Biology, 2018)
We present a 35-mm diameter skin-adhesive antenna intended to operate as a gateway to relay the low power signals from a sensor implanted in the body to an external base station (BS). Such a device would be useful in the context of body area networks (BANs) for continuous body-signal monitoring. The proposed adhesive repeater is of very low profile, and it is designed for dual-band operation at the ISM band (2.4 GHz) and in the ultrawideband (UWB) spectrum (4-10.6 GHz) using a single excitation port. The ISM band is used for in-body communication with the implants and the UWB band for off-body burst communication with the BS. The antenna consists of three layers that grant it compactness and performance robustness. We assess the in-body link between the repeater and a custom-designed miniaturized implantable probe antenna. The study is performed in the frequency domain with results showing adequate input impedance matching (s11 ? -10 dB) and robustness to different body parts. We extend the analysis to time domain by transmitting a synthetized medical signal between the two antennas. In addition, we evaluate the feasibility of an off-body link for burst communication. Again, the results indicate very good performance by the repeater antenna both in terms of impedance matching (s11 ? -10 dB) and preservation of time signals (fidelity ? 75%), which is relevant in impulse radio systems. To the authors' best knowledge, this is the first time this kind of dual-band adhesive antenna is being proposed for BANs, complete with performance tests using frequency- and time-domain figures-of-merit.